2021 IEEE International Symposium on Information Theory (ISIT) 2021
DOI: 10.1109/isit45174.2021.9517834
|View full text |Cite
|
Sign up to set email alerts
|

Decoding of Interleaved Linearized Reed-Solomon Codes with Applications to Network Coding

Abstract: Martínez-Peñas and Kschischang (IEEE Trans. Inf. Theory, 2019) proposed lifted linearized Reed-Solomon codes as suitable codes for error control in multishot network coding. We show how to construct and decode lifted interleaved linearized Reed-Solomon (LILRS) codes. Compared to the construction by Martínez-Peñas-Kschischang, interleaving allows to increase the decoding region significantly and decreases the overhead due to the lifting (i.e., increases the code rate), at the cost of an increased packet size. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…Thus, the proposed decoder can correct an overall number of insertions and deletions up to γ + δ ≤ n − k, which coincides with the decoding region of the decoders from [9], [12] and [13].…”
Section: (I)mentioning
confidence: 58%
See 1 more Smart Citation
“…Thus, the proposed decoder can correct an overall number of insertions and deletions up to γ + δ ≤ n − k, which coincides with the decoding region of the decoders from [9], [12] and [13].…”
Section: (I)mentioning
confidence: 58%
“…multishot network coding [2], [9], locally repairable codes [10], space-time codes [1] and code-based quantum-resistant cryptography [11]. Recently, it was shown that interleaved [12], [13] and folded [14] variants of LRS codes can be decoded beyond the unique decoding radius. The concept of row and column erasures, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…We state the interpolation problem and the algorithm in a general way using linear functionals over skew polynomials rings with arbitrary automorphisms and derivations. We show how the fast KNH interpolation can be applied to interpolation-based decoding of (interleaved) Gabidulin codes [33,52], interleaved linearized Reed-Solomon codes [7,8,14,37] and (interleaved) skew Reed-Solomon codes [7,8,13].…”
Section: Main Contributionmentioning
confidence: 99%
“…Further applications include the construction of space-time codes [34], locally repairable codes with maximal recoverability [42] (also known as partial MDS codes) and error control for multishot network coding [41]. Interpolation-based decoding of s-interleaved LRS codes, which allows for correcting errors beyond the unique decoding radius (up to s s+1 (n − k + 1)) in the sum-rank metric, was recently considered in [7]. In the following we show, how Algorithm 3 can be used to solve the interpolation step in the interpolation-based decoder for interleaved linearized Reed-Solomon (ILRS) from [7] efficiently.…”
Section: ⊓ ⊔mentioning
confidence: 99%
“…An [n, k, d] linear code C over F q is a k-dimensional subspace of F n q with minimum (Hamming) distance d and length n. If the parameters reach the Singleton bound, namely, d = n − k + 1, then C is maximum distance separable (in short, MDS). Especially, generalized Reed-Solomon (in short, GRS) codes are a well known class of MDS codes, it is very important in coding theory and applications [12], [8], [18], [20], [25], [6], [17], [24], [26], [10], [1], [7], [13], [5]. Other known MDS codes have been constructed from n-arcs in projective geometry [9], circulant matrices [22], Hankel matrices [22], or twisted Reed-Solomon (in short, TGRS) codes [2], [3].…”
Section: Introductionmentioning
confidence: 99%